(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to measure the grief response of kindergarten children and to identify the arrangement of the three domains of the grief response scale (threat of safety, loss of support, and emotional attachment) of kindergarten children. To achieve the research objectives, a proportional stratified random selection was made from the research community consisting of preparatory children in the six districts of Baghdad Governorate (Al-Rusafa Al-Karkh), and the main research sample consisted of 377 male and female children. For the purpose of measuring the research variables, a grief response scale was developed, which consisted of 33 items with three domains. The researcher tested two indicators of validity (apparent validity and constructive validity). As for the reliability, it was achieved by the researcher in several ways, as the reliability of the sadness response scale by the re-test method reached (0, 82). It reached (0, 87) by the Keider-Richardson method, and after applying the measures to the sample individuals and analyzing their responses statistically, using the t-test for one sample, the point-periodic correlation coefficient, the Pearson correlation coefficient, the habitual test, the chi-square test, the Cudor Richardson equation, and simple regression, The research showed that preschool children have a grief response. The highest percentage was obtained in the field of (threat to safety) on the sadness response scale.